2015
DOI: 10.1158/1538-7445.am2015-3545
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3545: Stromal selective targeting by uPAR retargeted oncolytic measles virus inhibits breast cancer progression

Abstract: Stromal cells in the tumor microenvironment play an important role in breast cancer progression. Strategies directed against stromal cell components have been investigated in the preclinical and clinical setting. However, few studies have focused on stromal targeting by oncolytic viruses. The urokinase receptor (uPAR) is overexpressed in tumor and stromal cells, and plays a critical role in tumor progression. The aim of this study is to evaluate the antitumor effects of stromal retargeted oncolytic measles vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…uPAR focuses uPA proteolytic activity on the cell membrane, mediates cell adhesion to vitronectin and activates cell signaling pathways by associating with cell surface molecules (4). Previous studies have demonstrated that uPAR has an increased expression in numerous malignant tumor types, including oral squamous cell, breast and pancreatic carcinomas (5)(6)(7), and it has been indicated to regulate a number of events, including angiogenesis, immune suppression and cell migration (8). Therefore, it has been considered that activation of uPAR serves a notable role in cancer cell invasion and is correlated with a poor long-term prognosis (9).…”
Section: Introductionmentioning
confidence: 99%
“…uPAR focuses uPA proteolytic activity on the cell membrane, mediates cell adhesion to vitronectin and activates cell signaling pathways by associating with cell surface molecules (4). Previous studies have demonstrated that uPAR has an increased expression in numerous malignant tumor types, including oral squamous cell, breast and pancreatic carcinomas (5)(6)(7), and it has been indicated to regulate a number of events, including angiogenesis, immune suppression and cell migration (8). Therefore, it has been considered that activation of uPAR serves a notable role in cancer cell invasion and is correlated with a poor long-term prognosis (9).…”
Section: Introductionmentioning
confidence: 99%